Media and Digital Modernism New Communication Environments - Kalaman, Sefer; Süslü, Bilal (Peter Lang GmbH, Internationaler Verlag der Wissenschaften, 2018)
New technologies have brought about radical changes in almost all areas of life. The best concept to describe this period is «digimodernism» in which there occur many transformations, from shopping to information, socialization to banking, education to communication. People, who become increasingly dependent on technology, computer and internet, are forced to attach themselves to the new social structure in a society that changes in parallel with digitalization. The Digimodern period has substantially affected the media as almost every point of life and caused great transformations. At this point, the main theme of the book is to reveal the structure of the media in the digital period.
Keywords: média; digitální média; komunikační technologie; media; digital media; communication technology; elektronické knihy; electronic books